2015
DOI: 10.1002/app.42188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonic assisted processing and clay nanofiller on dielectric properties and lithium ion transport mechanism of poly(methyl methacrylate) based plasticized polymer electrolytes

Abstract: Lithium ion conducting solid polymer electrolyte (SPE) films consisted of poly(methyl methacrylate) (PMMA) matrix with lithium perchlorate as a dopant ionic salt, poly(ethylene glycol) as plasticizer and montmorillonite clay as inorganic nanofiller have been prepared by classical solution casting and high intensity ultrasonic assisted solution casting methods. The X-ray diffraction study confirmed the amorphous structure of all these PMMA-based solid electrolytes and the clay nanosheets existed in exfoliated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
(170 reference statements)
0
12
0
Order By: Relevance
“…The spectra of M ′ and M ″ for the PVA– x wt % TiO 2 nanocomposites at 30 °C are depicted in Figure . We found that the M ′ values increased nonlinearly with increasing frequency; this suggested that it was the response of a bulk material because the electrode‐polarization‐effect‐dominated material had low‐frequency M ′ values close to zero . The M ″ spectra of the 1 and 3 wt % TiO 2 ‐based PNC films clearly exhibited sharp relaxation peaks in the low‐frequency region; these corresponded to the PVA main‐chain dynamics.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The spectra of M ′ and M ″ for the PVA– x wt % TiO 2 nanocomposites at 30 °C are depicted in Figure . We found that the M ′ values increased nonlinearly with increasing frequency; this suggested that it was the response of a bulk material because the electrode‐polarization‐effect‐dominated material had low‐frequency M ′ values close to zero . The M ″ spectra of the 1 and 3 wt % TiO 2 ‐based PNC films clearly exhibited sharp relaxation peaks in the low‐frequency region; these corresponded to the PVA main‐chain dynamics.…”
Section: Resultsmentioning
confidence: 84%
“…The M* (ω) spectra, which are the inverse of the dielectric function [ M* (ω) = 1/ɛ * (ω)] of the PNC materials, have been frequently studied to nullify the contribution of the electrode polarization effect in the bulk properties . The spectra of M ′ and M ″ for the PVA– x wt % TiO 2 nanocomposites at 30 °C are depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Figure (a–c) shows the variation of electric modulus real parts Mas a function of frequency for the unirradiated and irradiated PVA, (PVA‐CEA)‐MWCNT‐NH 2 , and (PVA‐CEA)‐MWCNT samples. The low values of electric modulus ( M ′) for all samples signifies the electrode polarization . The value of the real part ( M) at lower frequencies is low and it increases and a saturated is obtained when moving to the higher frequencies region.…”
Section: Resultsmentioning
confidence: 91%
“…The peaks of the electric modulus imaginary part ( M ″) with particular frequency is shown in Figure (a–c) for the unirradiated and irradiated PVA, (PVA‐CEA)‐MWCNT‐NH 2 , and (PVA‐CEA)‐MWCNT films. The effect of MWCNT decreases the relaxation time required for dipole orientation as shown in Figure (d) . Several polymer composite films exhibit a relaxation peak in their M ″ spectra below 1 MHz corresponding to the conductivity relaxation process .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation